Perceived skills for sports performance after primary hip arthroplasty: a cross-sectional study (2019)
Purpose: Recommendations arising from existing literature regarding restrictions and benefits of sporting activities after joint replacement surgery vary widely. As hip arthroplasty patients are becoming increasingly active, their expectations about post-operative function are constantly evolving. The aim of this study is to identify the perception of patients regarding their performance in sports activities after hip arthroplasty. Methods: This cross-sectional study included all patients undergoing primary hip arthroplasty, for any diagnosis, between January 2009 and January 2016. By applying a telephone survey, practice of sports before surgery, resumption after surgery, level of performance, and causes of non-resumption of sports activities were assessed. Results: Data of 531 patients were obtained. Of these, 13% were engaged in sports before surgery. The most frequently practiced sports were golf (27.5%) and tennis (22%). Of the 72 patients that practiced sports, only 44.4% (30 patients) returned to this activity after surgery. Nonetheless, 71% of these patients reported to have an equal or better athletic performance than before surgery. The main causes reported by patients not to return to sports were the fear of injury and recommendation of the surgeon. Conclusions: A significant number of patients return to sports after hip arthroplasty and most of them perceive a good athletic performance after surgery. These findings should enrich the pre-operative assessment of patient’s expectations, particularly for those who wish to resume physical activity. © 2019, SICOT aisbl.